Organisational change and development: Perspectives on theory and practice - Rees, Christopher J. (Journal of Business Economics and Management, 2008)
“Organisational change and development: Perspectives on theory and practice” Journal of Business Economics & Management, 9(2), p. 87-89 First published online: 14 Oct 2010